A proof of concept of a BioMEMS glucose biosensor using microfabricated SU-8 films - Psoma, Sotiria D. (Cranfield University, 2009)
The present project investigated and proved the concept of developing a novel BioMEMS glucose micro-biosensor using a simple one-step microfabrication process of the widely used SU-8 polymer. More specifically, the study focused on the investigation of the suitability of the SU-8 polymer as a matrix for enzyme immobilisation that is carried out during the microfabrication process. A comparative study between commercially available SU-8 and “customised” SU-8 solutions showed that the optimum concentration of photo-initiator for stress reduction can be achieved easier with “customised” SU-8 solutions. The most appropriate type of microstructure for the SU-8 matrix and the corresponding required microfabrication process were defined and encapsulation of the enzyme GOx in the SU-8 solution was accomplished. A detailed experimental investigation of the immobilised enzyme’s activity inside the SU-8 matrix, was carried out using amperometric detection of hydrogen peroxide in a 3-electrode setup. SU-8 films were immersed in a buffer solution and the platinum working electrode was brought in close contact with the film. Films without enzyme showed negligible variation in current upon the addition of glucose, as opposed to films with encapsulated enzyme which showed a very clear increase in current. Experiments using films of increased thickness or enzyme concentration, showed a higher response, thus proving that the enzyme remained active not only on the film’s surface, but inside the matrix as well. In the fluorescence spectroscopy experiments, the utilisation of the tris (4,7- diphenyl-1,10-phenanthroline) ruthenium(II) dichloride oxygen indicator, which was also captured in the polymer matrix during the microfabrication process, was proven to be very sensitive to glucose concentration changes during the glucose oxidation and there was no photo-bleaching. The experimental investigations proved that the proposed concept of using SU-8 matrices for the immobilisation of biomolecules, is a valid proposal for the construction of a BioMEMS glucose biosensor. An important outcome was the successful immobilisation of glucose oxidase in SU-8 microfabricated structures. The enzyme still showed activity despite the “hostile” conditions during microfabrication The proof of principle of enzyme immobilisation in SU-8 films opens up new possibilities for combining BioMEMS with biosensors and organic electronics.